Egg Parasitoids in Agroecosystems with Emphasis on Trichogramma - Consoli, Fernando L.; Parra, José R. P.; Zucchi, Roberto A. (Progress in Biological Control,, 2010)
Egg Parasitoids in Agroecosystems with emphasis on Trichogramma was conceived to help in the promotion of biological control through egg parasitoids by providing both basic and applied information. The book has a series of chapters dedicated to the understanding of egg parasitoid taxonomy, development, nutrition and reproduction, host recognition and utilization, and their distribution and host associations. There are also several chapters focusing on the mass production and commercialization of egg parasitoids for biological control, addressing important issues such as parasitoid quality control, the risk assessment of egg parasitoids to non-target species, the use of egg parasitoids in integrated pest management programs and the impact of GMO on these natural enemies. Chapters provide an in depth analysis of the literature available, are richly illustrated, and propose future trends. The large number of contributors in several fields of Entomology makes this book the most comprehensive source of information for students and researchers working on egg parasitoids, biological control practitioners interested in applying these natural enemies in biocontrol programs or business managers focused in their mass production and commercialization.